2015
DOI: 10.1242/dev.123653
|View full text |Cite
|
Sign up to set email alerts
|

Neural retina identity is specified by lens-derived BMP signals

Abstract: The eye has served as a classical model to study cell specification and tissue induction for over a century. Nevertheless, the molecular mechanisms that regulate the induction and maintenance of eye-field cells, and the specification of neural retina cells are poorly understood. Moreover, within the developing anterior forebrain, how prospective eye and telencephalic cells are differentially specified is not well defined. In the present study, we have analyzed these issues by manipulating signaling pathways in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 61 publications
1
48
0
Order By: Relevance
“…This same study showed that adding BMP7 or the combination of BMP4 and BMP7 to Lhx2 −/− head cultures was sufficient to induce Sox2 expression in surface ectoderm (Yun et al, 2009). Other studies have also demonstrated an essential role for BMP4/7 signaling in early stages of lens development (Furuta and Hogan, 1998;Murali et al, 2005;Pandit et al, 2015;Wawersik et al, 1999). By contrast, our study indicated FGF signaling as perhaps the major mediator in Lhx2 regulation of lens maturation.…”
Section: Discussionsupporting
confidence: 56%
“…This same study showed that adding BMP7 or the combination of BMP4 and BMP7 to Lhx2 −/− head cultures was sufficient to induce Sox2 expression in surface ectoderm (Yun et al, 2009). Other studies have also demonstrated an essential role for BMP4/7 signaling in early stages of lens development (Furuta and Hogan, 1998;Murali et al, 2005;Pandit et al, 2015;Wawersik et al, 1999). By contrast, our study indicated FGF signaling as perhaps the major mediator in Lhx2 regulation of lens maturation.…”
Section: Discussionsupporting
confidence: 56%
“…In the lens-forming ectoderm, BMP expression is negatively autoregulated [135] and this is independent of Smad1, Smad5, or Smad4 [52]. BMP signals stemming from the lens specify the neuroretina [136], and loss of BMP4 in the optic vesicle is detrimental for lens formation along with the neuroretina being converted into the RPE [54]. It appears that expression of BMPs in the dorsal optic vesicle is stabilized by Wnt signals from the ectoderm via β-catenin-independent and GSK3β-dependent pathway [137].…”
Section: Lens Morphogenesis and Gene Regulatory Networkmentioning
confidence: 99%
“…At an earlier stage in chicken, the pre-lens ectoderm is required for optic cup morphogenesis (Hyer et al, 2003). Chicken studies also suggest that lens ectoderm-derived Bmp activity specifies retinal cells (Pandit et al, 2015). Further, Dr. David Beebe’s findings indicate that the lens is necessary for organizing the anterior segment through control of corneal endothelium (Beebe and Coats, 2000).…”
Section: Future Of Lens Research: Toward Lens Systems Biologymentioning
confidence: 99%